2004
DOI: 10.1007/s10815-004-8758-2
|View full text |Cite
|
Sign up to set email alerts
|

Monozygotic Twin Birth After the Transfer of a Cleavage Stage Embryo Resulting from a Single Pronucleated Oocyte

Abstract: Purpose : To present a case involving the transfer of a single pronucleated oocyte resulting in a monozygotic twin pregnancy. Method : A descriptive case report of a single patient. Results : The patient conceived and was found to have a monochorionic diamnionic pregnancy which resulted in the birth of normal identical twin boys at 32 weeks of gestation. Conclusions : The case report addresses an issue that has not received proper attention in the literature. It illustrates that observing a single PN in an ooc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Similar reports on neonatal data derived from 1PN embryos in cIVF and ICSI have been reported in the literature [4,5,7,8]. Gras and Trounson [7] and Reichman et al [5] have reported similar findings on normal birth weight, the weeks of gestation, and a birth of a healthy child.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Similar reports on neonatal data derived from 1PN embryos in cIVF and ICSI have been reported in the literature [4,5,7,8]. Gras and Trounson [7] and Reichman et al [5] have reported similar findings on normal birth weight, the weeks of gestation, and a birth of a healthy child.…”
Section: Discussionsupporting
confidence: 77%
“…Gras and Trounson [7] and Reichman et al [5] have reported similar findings on normal birth weight, the weeks of gestation, and a birth of a healthy child. Staessen et al [4] and Dasig et al [8] also described the delivery of healthy babies without neonatal data. Previous studies regarding live birth babies derived from 1PN embryos have reported no major malformations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occasionally, only one pronucleus (1PN) is observed in oocytes. The frequencies of the occurrence of 1PN zygotes ranged from 1.6% to 7.7% [1]. The mechanism of 1PN zygotes has been extensively studied as: a) asynchrony of the pronuclear appearance [2][3][4] or b) the male and female pronuclear fusion together [5,6], which will result in chromosomally normal embryos; while c) androgenetic or gynogenetic parthenogenesis, which will lead to haploid embryos [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of 1PN zygotes are incapable of further development, a small number develop to the blastocyst stage. Moreover, they successfully progress to a live birth in cases where no other embryos exist of better quality [30][31][32] and despite the low pregnancy rate. Nevertheless, because of the uncertainty of their genetic normality, transferring such embryos is controversial among ART laboratories.…”
Section: Aberrant Behavior Of Female Pn (Fpn) During the Pronuclear Smentioning
confidence: 99%